Correlation of Ultrasonographic Findings with Estimated Glomerular Filtration Rate in Chronic Kidney Disease - Kharel, Amrit; Shrestha, Shreejana; Karki, Dan Bahadur (Journal of National Heart and Lung Society Nepal, 2024)
Background: Chronic Kidney Disease (CKD) is a condition characterized by kidney damage for three or more months or Glomerular Filtration Rate (GFR) less than 60ml/minute/1.73m2 for three or more months with or without kidney damage. Ultrasonography is the noninvasive imaging modality to determine the renal morphology. The aim of this study was to find the correlation of ultrasonographic parameters with estimated Glomerular Filtration Rate (eGFR) in CKD patients visiting a tertiary hospital. Methods: This observational cross-sectional study was carried at Patan Hospital in thirty-five CKD diagnosed cases above the age of 18 years. Renal sonographic parameters like renal length, width, parenchymal thickness, and cortical echogenecity grade were obtained during ultrasonography. eGFR was calculated from CKD-EPI formula after obtaining serum creatinine. Ultrasonographic parameters were compared with eGFR using Spearman correlation test and Kruskal Wallis test was used to check difference in median eGFR among different echogenicity grades. Results: Statistically significant moderate positive correlation was seen between eGFR and parenchymal thickness (rs = 0.51, p<0.05) and eGFR and length (rs = 0.46, p<0.05) but weak positive correlation was seen between eGFR and width (rs = 0.3, p<0.05). A statistically significant relationship was also seen between eGFR and renal cortical echogenecity grade (p<0.05). Conclusion: Renal parenchymal thickness has maximum positive correlation with eGFR than other parameters to measure renal dimensions like renal length and width. Hence, renal parenchymal thickness is a better parameter to measure renal dimension in patients with CKD.